Microdialysis-Assessed Exercised Muscle Reveals Localized and Differential IGFBP Responses to Unilateral Stretch Shortening Cycle Exercise - Nindl, Bradley C.; Ahtiainen, Juha; Gagnon, Sheila S.; Taipale, Ritva S.; Pierce, Joseph R.; Martin, Brian J.; Beckner, Meaghan E.; Lehti, M.; Häkkinen, Keijo; Kyröläinen, Heikki (Frontiers in Endocrinology, 2020)
Microdialysis allows for a preview into local muscle metabolism and can provide physiological insight that blood measurements cannot. Purpose: To examine the potential differential IGF-I system regulation in interstitial fluid during unilateral stretch shortening cycle exercise. Methods: 10 men (26 ± 7 year) performed unilateral jumping [stretch shortening cycle (SSC) exercise at 50% of optimal jump height] until volitional fatigue on a sled apparatus. Biological sampling took place using a catheter inserted into an antecubital vein (serum), and 100 kDa microdialysis probes inserted into the thigh muscle of each exercise/control leg (dialysate). Serum was drawn before (Pre; −3 h) and after SSC [Post I (+0 h), II (+3 h), or III (+20 h)]; dialysate was sampled for 2 h before (Pre), during/immediately after (Ex), and 3 h into recovery (Rec) following SSC. IGF-I system parameters (free/total IGF-I and IGFBPs 1–6) were measured with immunoassays. Interstitial free IGF-I was estimated from dialysate IGF-I and relative recovery (ethanol) correction. Data were analyzed with repeated measures ANOVA. Results: Serum total IGF-I remained elevated +3 h (Post II: 182.8 ± 37.6 vs. Pre: 168.3 ± 35.0 ng/mL, p < 0.01), but returned to baseline by +20 h (Post III vs. Pre, p = 0.31). No changes in serum free IGF-I were noted. Serum BP-1 and −3 increased over baseline, but not until + 20 h after SSC (Post III vs. Pre: 7.6 ± 4.9 vs. 3.7 ± 2.3 and 1,048.6 ± 269.2 vs. 891.4 ± 171.2 ng/mL, respectively). We observed a decreased serum BP-6 +3 h after SSC (p < 0.01), followed by a return to baseline at +20 h (p = 0.64 vs. Pre). There were no exercise-induced changes in serum BP-2, −4, or −5. Unlike serum, there were no changes in dialysate or interstitial free IGF-I in either leg (p > 0.05). Dialysate BP-1 remained increased in both exercise and control legs through 3 h into recovery (Rec vs. Pre, p < 0.01). Dialysate BP-3 also demonstrated a prolonged elevation over Pre SSC concentrations, but in the exercise leg only (Ex and Rec vs. Pre, p < 0.04). We observed a prolonged decrease in dialysate BP-5 (Ex and Rec vs. Pre, p < 0.03) and an increase in BP-4 IP in the exercise leg only. There were no changes relative to Pre SSC in dialysate BP-2 or −6. Conclusions: Unilateral exercise drives differential regulation of the IGF-I system at both local and systemic levels. More specifically, this is the first study to demonstrate that localized exercise increases IGFBP-3, IGFBP-4 and decreases in IGFBP-5 in muscle interstitial fluid.